Development of a Secure Mobile Cloud Computing Model for Universities Services - Elfurgani, ZBM; Bin Abdullah, I (Amer Scientific Publishers, 2024)
The learning and technical services that are provided by universities to students are based on face to face approach. This approach consumes time, expenses, and efforts to accomplish services effectively. Information systems were adopted widely in universities to provide student services electronically in less time and efforts. The main problem of information systems is that the services provided in specific time per day and the students need to visit a specific location to accomplish the services. Information systems based on cloud computing technology to address these issues through providing services anytime and anywhere. The performances of cloud computing services are affected by the computing devices that the students own. Mobile devices such as smart phones allow the students to accomplish their services in real time while the traditional PCs are usually allocated in students' homes, which prevent the students from complete their services when they outside. There are many challenges facing the universities to adopt mobile cloud computing technology to serve the student's needs. Firstly, data security should be assured due to online transferring using wireless networks. Online data transferring increase the opportunities of data attacking. Secondly, the service performance of mobile cloud computing effecting by many variables like mobile device features, type of services, and transferred data sizes. This requires useful analysis of services and mobile device features to assure high level of service performance. This research aims to develop mobile cloud computing model to increase the performance of provide services to university students. USIM considered as an empirical case study of universities. The construction of the proposed model is in two main folds; (1) analyze the security services that should be adopted to secure the transferred data security and privacy, and (2) analyze the most important services that could provide by USIM using mobile cloud computing and consequently analyze the features of mobile devices based on the provided service aspects.